Platelet-derived extracellular vesicles ameliorate intervertebral disc degeneration by alleviating mitochondrial dysfunction - Zhanqiu Dai; Chen Xia; Tingxiao Zhao; Haoli Wang; Hongsen Tian; Ouyuan Xu; Xunbin Zhu; Jun Zhang; Pengfei Chen (Materials Today Bio, 2023)
Mitochondrial dysfunction causes the production of reactive oxygen species (ROS) and oxidative damage, and oxidative stress and inflammation are considered key factors causing intervertebral disc degeneration (IVDD). Thus, restoring the mitochondrial dysfunction is an attractive strategy for treating IVDD. Platelet-derived extracellular vesicles (PEVs) are nanoparticles that target inflammation. Moreover, the vesicles produced by platelets (PLTs) have considerable anti-inflammatory effects. We investigate the use of PEVs as a therapeutic strategy for IVDD in this study. We extract PEVs and evaluate their properties; test their effects on H2O2-induced oxidative damage of nucleus pulposus (NP) cells; verify the role of PEVs in repairing H2O2-induced cellular mitochondrial dysfunction; and demonstrate the therapeutic effects of PEVs in a rat IVDD model. The results confirm that PEVs can restore impaired mitochondrial function, reduce oxidative stress, and restore cell metabolism by regulating the sirtuin 1 (SIRT1)-peroxisome proliferator-activated receptor gamma coactivator 1α (PGC1α)-mitochondrial transcription factor A (TFAM) pathway; in rat models, PEVs retard the progression of IVDD. Our results demonstrate that the injection of PEVs can be a promising strategy for treating patients with IVDD.